1995
DOI: 10.1021/jf00049a001
|View full text |Cite
|
Sign up to set email alerts
|

Flavanone and Nootkatone Levels in Different Varieties of Grapefruit and Pummelo

Abstract: The effects of variety, rootstock, and geographical location were studied as to their effects on secondary metabolite production in grapefruit and pummelo. The concentration of the flavanones narirutin, naringin, and neohesperidin and of the sesquiterpene nootkatone, which is principally responsible for the grapefruit's aroma, varies during h i t development. The highest flavanone levels are detected during the juvenile stages of fruit development, while nootkatone expression is associated with the processes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
46
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 22 publications
(29 reference statements)
9
46
0
2
Order By: Relevance
“…Thus, the data in the literature are inconclusive as to the evolutionary source of valencene production, but suggest that putative enzymes converting valencene to nootkatone were inherited from pummelo. Similarly, the bitter¯avanone neohesperidoside¯avor compounds and their corresponding biosynthetic enzymes are distinctly associated with species/varieties of pummelo origin (Bar-Peled et al, 1991;Lewinsohn et al, 1989;Ortuno et al, 1995).…”
Section: Level Ofmentioning
confidence: 99%
“…Thus, the data in the literature are inconclusive as to the evolutionary source of valencene production, but suggest that putative enzymes converting valencene to nootkatone were inherited from pummelo. Similarly, the bitter¯avanone neohesperidoside¯avor compounds and their corresponding biosynthetic enzymes are distinctly associated with species/varieties of pummelo origin (Bar-Peled et al, 1991;Lewinsohn et al, 1989;Ortuno et al, 1995).…”
Section: Level Ofmentioning
confidence: 99%
“…The highest levels of these secondary compounds were found in young developing fruits (3)(4)(5)(6)(7), although it has been suggested that some polymethoxyflavones might be related to the maturation phase of fruit in some Citrus species (7).…”
Section: Introductionmentioning
confidence: 99%
“…20 Naringin (4',5,7-trihydroxyflavanone-7-rhamnoglucoside), aglycone of naringenin is the predominant flavanone synthesized by grapefruit (Citrus paradisi) and is responsible for the bitter taste of grapefruit juices. 21 Naringin (NIN) was first discovered by De Vry in the flowers of grape fruit trees growing in Java in 1857. The name naringin is probably derived from the Sanskrit term "narangi" meaning "orange".…”
Section: Introductionmentioning
confidence: 99%